Kesantunan Berbahasa Terhadap Nilai Budaya Suku Bugis-Makassar: Suatu Telaah Sosiopragmatik - Room, Rusdi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2025)
This study aims to describe and analyze the practice of linguistic politeness in relation to the cultural values of the Bugis-Makassar community, particularly the values of Sipakatau, Sipakalebbi/Siakalabbiri, Siri’, and Pangngaderreng/Pangngadakkang. The research employs a qualitative approach with a sociopragmatic design integrated with an ethnography of communication perspective. Data were collected through participant observation, in-depth interviews, and documentation of speech events within family and educational settings in South Sulawesi. Data analysis involved data reduction, categorization of politeness strategies, and contextual interpretation using the politeness theory of Penelope Brown and Stephen C. Levinson, contextualized within the concept of collective dignity embedded in Bugis-Makassar culture. The findings indicate that linguistic politeness practices continue to reflect strong local cultural values. Address systems, honorific expressions, and indirect communication strategies function as mechanisms for maintaining face and social dignity. The value of Siri’ serves as the primary foundation for regulating speech behavior and preserving social harmony, while the principles of Sipakatau and Sipakalebbi are manifested in lexical choices that convey respect and honor toward interlocutors. However, modernization, shifting interaction patterns, and the declining use of local languages have contributed to the weakening internalization of politeness values among some younger generations. This study underscores that understanding politeness practices within the Bugis-Makassar community requires the integration of universal politeness theory and local cultural frameworks. Theoretically, this research contributes to the development of sociopragmatic studies grounded in local wisdom, while practically it provides a conceptual foundation for strengthening character education and cultural preservation through ethical communication practices.